SIMULASI TATA GUNA LAHAN TERHADAP KUALITAS AIR SUNGAI dengan METODE INDEKS PENCEMARAN ( Studi Kasus : Sungai Tuntang, Jawa Tengah ) - Anggun Hera S (Jurnal Teknik Lingkungan, 2013)
Tuntang River is a main river of Tuntang’s watershed which is located in Central Java. Administratively, Tuntang River covers seven districts with a total area of ± 139 km long rivers. Tuntang River’s stream go through various hue environments namely forest, residential, agricultural and moor which potentially reduce the quality of agency ait Tuntang River. The determination of Tuntang River water quality used River Pollution Index method. The water quality monitoring carried out in five river segments. The results were obtained using the pollution index calculation with the scorings as follow: Segment 1 = Class 1: 1.56; Grade II: 1.54; Grade III: 1.54; Grade IV: 0.64. Segment 2 = Class I: 0.9, Class II: 0.88; Grade III: 0.87; Grade IV: 0.64. Segment 3 = Class I: 0.67; Grade II: 0.66; Grade III: 0.65; Grade IV: 0.64. Segment 4 = Class I: 0.67; Grade II: 0.67; Grade III: 0.66; Grade IV: 0.65. Segment 5 = Class I: 0.75; Grade II: 0.68; Grade III: 0.66; Grade IV: 0.66.The water quality is categorized quite well because the water meet the quality standards for rivers class I designation.   The land use in every segment of the Watershed (DAS) Tuntang can affect the water quality. The changes of the land use giving influence for the water quality of Tuntang River, the simulation of addition of the residential land can improve the water quality corresponding the IP value become worse, the simulated reduction in agricultural land can degrade water quality corresponding IP value better. The simulation of addition of the residential land also caused the improvement of the water BOD. From the calculation of water quality by using Pollution Index based on the simulation of addition of the residential land, it was known that the quality of Tuntang River water had a quality status to Meet Quality Standards with Cemar Lightweight IP value between 3.89 to 0.66. To stimulate the reduction of agricultural, it is known that the water of Tuntang River had a quality of Meet Quality Standards with Cemar Lightweight IP value between 1.66 to 0.66.